2012
DOI: 10.1007/s13105-012-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and arterial blood pressure alterations after exposure to acetaminophen with a potential role of Nigella sativa oil in adult male rats

Abstract: Hepatic injury by acetaminophen (APAP) has been extensively studied, although the alterations of renal functions and arterial blood pressure (ABP) after APAP exposure are still uncertain, and the impact of Nigella sativa oil (NSO) in this case is poorly defined. Sixty adult male albino rats were involved in two sets of experiments. The first was exposed to a single high dose of APAP (2.5 g/kg) orally preceded by 4 ml NSO/kg orally, while the second received 750 mg APAP/kg/day orally for seven consecutive days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…This effect may trigger multiple adaptive processes in the hyper-functioning remaining nephrons, most notably the augmented rates of Na + reabsorption that lead to hypernatremia. On the other hand, the observed increase in the serum K + level in the present Gly model of RM-ARF, which is correspondingly reported previously [ 33 , 36 ], could be explained by the direct release of the intracellular K + from the damaged muscles [ 37 ]. Remarkably, this hyperkalemia has not been observed in other studies using different models of ARF rather than RM-ARF [ 35 , 38 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This effect may trigger multiple adaptive processes in the hyper-functioning remaining nephrons, most notably the augmented rates of Na + reabsorption that lead to hypernatremia. On the other hand, the observed increase in the serum K + level in the present Gly model of RM-ARF, which is correspondingly reported previously [ 33 , 36 ], could be explained by the direct release of the intracellular K + from the damaged muscles [ 37 ]. Remarkably, this hyperkalemia has not been observed in other studies using different models of ARF rather than RM-ARF [ 35 , 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…The decreased serum Na + level observed in the current Gly model of RM-ARF, and before [ 33 ], indicated this tubular dysfunction with a decreased Na + reabsorption. However, a significant increase in serum Na + levels was reported in other studies [ 34 , 35 ]. This may be due to acute tubular necrosis that could lead to a decrease in the number of functioning nephrons.…”
Section: Discussionmentioning
confidence: 66%
“…Low HDL-C/high TAGs of T2DM significantly predicted the incidence of vascular events [44]. Ahmed et al (2013) claimed that glycemic control and dyslipidemia in diabetic patients correlate each other and are interdependent [45].…”
Section: Discussionmentioning
confidence: 99%
“…The antihypertensive principal TQ and other constituents of N. sativa are also protective agents against the chromosomal aberrations induced by schistosomiasis (Aboul-El-Ela 2002 ; El Tahir et al 1993a ). These compounds are used in the control of arterial blood pressure, anticholinergic, antihistaminic, tracheal relaxation, control of asthma and in the treatment of other allergic diseases (Ahmed and El-Mottaleb 2013 ; Al-Majed et al 2001 ; Boskabady et al 2004 ; Kalus et al 2003 ; Steinmann et al 1997 ) (Fig. 4 ).…”
Section: Biological Activities Of Nigella Sativamentioning
confidence: 99%
“…The chemical composition and biological properties of Nigella sativa L. have previously been reviewed (Khan 1999 ; Paarakh 2010 ; Ahmed and El-Mottaleb 2013 ). In the previous review (Khan 1999 ) were reported the large variety of organic compounds that are present in the seeds of N. sativa L. The seeds of this herb are used in the Middle East and South Asian countries for the treatment of a large variety of ailments and are accepted as a panacea.…”
Section: Introductionmentioning
confidence: 99%